A Fundamental Investigation of Decarburization Reactions in the Argon–Oxygen Decarburization Converter Using Coupled Computational Fluid Dynamics and Thermodynamics Databases. Issue 12 (30th June 2022) - Chanouian, Serg; Ahlin, Björn; Tilliander, Anders; Ersson, Mikael
Abstract : Metallurgical converters such as the argon–oxygen decarburization (AOD) converter generally utilize gas blowing for the mixing and refinement of liquid steel. Due to the harsh environment of the complex and opaque system, it is common practice to study the stirring of the process through physical and numerical models. Effective mixing in the bath has an important role in refinement such as decarburization and has been vividly studied before. However, high‐temperature chemical reactions that also play a major role are sparsely investigated. With the help of modeling, a computational fluid dynamics model coupled with chemical reactions is developed, allowing the study of both dynamic fluid transport and chemical reactions. Herein, the chemical reactions for a single gas bubble in the AOD are investigated. The study shows that a 60 mm oxygen gas bubble rapidly reacts with the melt and is saturated with carbon in 0.2–0.25 s at low‐pressure levels. The saturation time is affected by the pressure and the composition of the injected gas bubble. The impact of ferrostatic pressure on the reactions is more significant at larger depth differences. Abstract : A coupled thermodynamic and fluid transport model on a dynamic bubble in liquid steel is developed to fundamentally investigate pressure differences in decarburization reactions. The impact of ferrostatic pressure is more significant at larger depth differences. A bubble closer to the surface is saturated at higher carbon levels due to the lowered partial pressure of the elements in the gas.